Ulterior Motives: 2023-2024 ACM Athena Lecturer Margo Seltzer recalls the motivations behind the development of the Berkeley DB database software library, and other achievements during her career. - Hoffmann, Leah (Communications of the ACM, 2023)
An interview with lecturer Margo Seltzer is presented which addresses topics such as the motivations behind the creation of the Berkeley DB database software library by Seltzer, Keith Bostic, and Mike Olson. The Sleepycat Software firm and fundraising are assessed, as well as open-source dual licenses, data provenance, and collections of certain types of data.